THE INFLUENCE OF FIRM FINANCIAL PERFORMANCE ON STOCK PRICE OF PROPERTY AND REAL ESTATE COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) - Ratri Anggarani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to determine the influence of financial ratios and economic value added on stock price of property and real estate companies listed in IDX. There are two independent variables; financial ratios and economic value added (EVA). The dependent variable is stock price. The research uses purposive sampling method for selecting the samples resulted in 14 qualified companies during 2012-2014. Analysis of the data in this study using multiple regression analysis. Test results shows the variable that significantly influences the stock price is Financial Ratios. This finding explains that earning per share and price earning ratio is successful for being the proxy of profitability that logically be capable in showing the high value relevance with the expectation of stock price returns to investors also high. It means that EPS and PER have been able to influence the decision of managers or users of other financial statements to support their expectations of the results to be obtained. It can be concluded that the financial manager of the company has been able to fulfill the expectations of shareholders which is to manage the assets optimally so as to produce the desired profit. Meanwhile, Economic Value Added (EVA) has a insignificant influence on stock price. It means that when the EVA value of company increase, not necessarily the return will be received by investors will also rise, and vice versa. This shows that EVA analysis is not used as a basis for decision making for investors to make purchases or disposals of the company's shares and also not used by the management company in decision- making for dividend.Keywords: financial ratios, economic value added, stock price.